The Theory of Generations Importance for Implementing Medical and Social Needs of Children and Their Families in Russia - Leonid P. Chicherin; Valery Yu. Albitskiy; Vladimir O. Shchepin ("Paediatrician" Publishers LLC, 2022)
Fundamental principles of the theory of generations and its Russian version, which have been widely distributed in the last three decades especially in psychological science have been analyzed. The author's opinion on the real possibility of its implementation in the practice for protecting the health of younger generation of the country considering the degree of formation in family and in, educational organization of the child's life values, behavior and his own health attitude, is presented. The application perspectiveness of the Theory in the medical and organizational, psychological, ethical, and deontological, legal plan on the model of social patronage in the family, medical and social work, especially in the pediatric primary care, acquaintance with the living conditions specialty, education, development and growing up, intrafamilial relations, "problems of fathers and children" are presented.